Alternatif Penyelesaian Waris Pengganti Di Indonesia - Ahmad Insya' Ansori; Moh Ulumuddin (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2019)
The difference between salaf scholars and modern scholars about the successor to successors. Salaf scholars state that